Effect of Candelilla Wax Concentration and Zinc Oxide Nanoparticles (NP-ZnO) on the Physical and Mechanical Properties of Carrageenan-Based Edible Films - Setyadi Gumaran; Linda Safitri; Zunanik Mufidah (Jurnal Keteknikan Pertanian Tropis dan Biosistem, 2026)
This study focuses on the analysis of carrageenan-based edible films with the addition of candelilla wax and zinc oxide nanoparticles (NP-ZnO) and their effects on physical and mechanical properties. The edible films were formulated using kappa carrageenan and additional ingredients such as Tween 60, Span 60, glycerol, and distilled water. This research used a completely randomized design (CRD) consisting of two factors NP-ZnO as the first factor with consentrate levels of 1, 2, 3%, resulting in 9 treatment combinations with 3 replications. The data analysis was performed using the software minitab to obtain mean values and standard deviations, which were presented in graphical form for the physical and mechanical property results. The edible film was cast into plastic petri dishes nd then dried in an oven at 50 °C for 2 days. The observed parameters included thickness, color, water vapor transmission rate (WVTR), water absorption capacity (WAC), water solubility (WS), tensile strength, and elongation. The results showed that the addition of candelilla wax and NP-ZnO affected the physical and mechanical properties of the film. Increasing the concentration of candelilla wax and NP-ZnO increased the thickness value from 0.078 to 0.1 mm and increased the ?E value from 19.67 to 23.57. Meanwhile, the WAC value decreased from 82.65% to 63.95%, the WS value decreased from 84.43 to 66.80%, and the WVTR value decreased from 22.5 to 19.56 5 g/m2.d. in contrast, tensile strength increased from 1.831 to 4.6 MPa, while the elongation value decreased from 48.93 to 28.25%.